PENGARUH MEDIA POWER POINT INTERAKTIF TERHADAP PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Suharsono; Muhammad Iqbal (STIT Muhammadiyah Paciran Lamongan, 2025)
Low learning outcomes in Islamic Religious Education (PAI) are often associated with students’ lack of motivation and engagement during the learning process. This study aims to analyze the effect of using interactive PowerPoint media on improving students’ learning outcomes. The research employed a quantitative approach through a Classroom Action Research (CAR) method conducted in two cycles. The subjects consisted of 22 fourth-grade elementary students. Data were collected using learning outcome tests (pre-test and post-test), observation sheets, and teacher interviews. The findings revealed a substantial enhancement in students’ learning outcomes, with the percentage of learning mastery rising from 27.27% in the pre-cycle to 63.64% after implementing interactive PowerPoint media. The Product Moment correlation test showed a calculated r value of 0.964, exceeding the r table value of 0.423, while the t-test yielded a calculated t value of 16.165, greater than the t table value of 1.717, which signifies a strong and significant correlation between the use of interactive PowerPoint media and students’ learning outcomes in Islamic Education (PAI). The determination test also revealed that 92% of the improvement in learning outcomes was influenced by the use of interactive PowerPoint, while 8% was affected by other factors. Therefore, the use of interactive PowerPoint has been proven to serve as an effective instructional medium for improving students’ comprehension, motivation, and participation in Islamic Religious Education.